El recurso extraordinario de revisión contra las resoluciones sancionatorias disciplinarias de la junta de resolución de conflictos del distrito 06d01 de educación Chambo – Riobamba, dentro de los sumarios administrativos instaurados a docentes - Puente Riofrio, Luis Alberto (2022)
ABSTRACT: The research work entitled "Ergonomic risk management in the jobs of the operational staff of the EERSA-Agencia Alausí in the period 2022" exposes the application of procedures that identify and ergonomically evaluate the work context based on the analysis of each one. The processes and activities that compose it thus contribute to sound risk management applied to technical personnel. The investigative methodology was mixed, applying a qualitative, quantitative, and observational analysis, adapting a survey between the Nordic Questionnaire and the ERGOPAR Method to collect information. The observation of the activities carried out by the staff was evidenced from their workplace for postural analysis. The analysis allows discovering the causes that affect the health of workers, and their performance, where the predominant factors are: physical overexertion, repetitive movements, postural load, etc.; they were analyzed using RULA, REBA, OWAS, JSI, and GINSST ergonomic evaluation tools, conclusively demonstrating that there are permanent risks in daily operational performance; the same ones that, using a technical analysis accompanied by engineering controls, allow to establish anticipated corrections to an occupational disease. The application results make EERSA-Alausí Agency collaborators direct beneficiaries, with the implementation of an action plan and corrective measures, minimizing negative impacts and improving individual and collective work performance. Keywords: Risk Management, Factors, Postural Analysis, Ergonomic Evaluation, Corrective Measures.